Biomechanical Analysis of Tennis Spin Serve Technique Using Kinovea in Beginner Athletes in South Sulawesi - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; Yusnadi; Andi Rizal; Hasbi Asyhari (Journal Physical Health Recreation (JPHR), 2025)
This study aims to analyze the spin serve technique in novice tennis players, with an emphasis on trunk rotation and dynamic balance, using Kinovea motion analysis software. A total of 30 novice athletes, aged 14–16 years, from South Sulawesi, became the subjects in this study. Data were collected through high-speed video recording from three angles and analyzed using Kinovea to observe seven stages of tennis court service, namely: coiling, ball toss, backswing, uncoiling, strike zone, follow-through, and fall-in. The results showed that the effective spin serve technique is greatly influenced by optimal trunk rotation with an average of 8.32 and good dynamic balance with an average of 72.03. These findings indicate that players with proper trunk rotation and balance tend to produce more accurate and powerful serves. Kinovea has been proven effective as an objective tool in evaluating the quality of the spin serve technique.